Implementation of the SMART Algorithm in Determining Patient Satisfaction Levels with Outpatient Services - Patar Simbolon; Muhammad Zarlis; Sundari Retno Andani; Fitri Anggraini (JOMLAI: Journal of Machine Learning and Artificial Intelligence, 2023)
This study aims to implement the SMART algorithm in determining the level of patient satisfaction with outpatient services at Vita Insani Hospital Pematangsiantar. This study uses four evaluation criteria, namely speed of service, friendliness of staff, clarity of information, and comfort of the room. There are nine alternatives evaluated, namely registration, polyclinic, doctor, cashier, laboratory, radiology, pharmacy, emergency room, and security guard. This study uses the SMART method (Simple Multi-Attribute Rating Technique) in determining the level of patient satisfaction with outpatient services. Calculations are performed either manually or computerized. The results showed that the two calculation methods yielded the same results, namely alternative A9 (Security Guard) was selected as an alternative that needed to improve its services in improving outpatient services at Vita Insani Hospital. By using the SMART algorithm, it is hoped that the hospital can identify service areas that need to be improved to increase patient satisfaction in outpatient services. This research provides valuable information for hospital management in making strategic decisions to improve service quality and meet patient expectations.